Taste Metaphors Ground Emotion Concepts Through the Shared Attribute of Valence - Avery, Jason A.; Liu, Alexander G.; Carrington, Madeline; Martin, Alex (Frontiers in Psychology, 2022)
‘Parting is such sweet sorrow.’ Taste metaphors provide a rich vocabulary for describing emotional experience, potentially serving as an adaptive mechanism for conveying abstract emotional concepts using concrete verbal references to our shared experience. We theorized that the popularity of these expressions results from the close association with hedonic valence shared by these two domains of experience. To explore the possibility that this affective quality underlies the semantic similarity of these domains, we used a behavioral ‘odd-one-out’ task in an online sample of 1059 participants in order to examine the semantic similarity of concepts related to emotion, taste, and color, another rich source of sensory metaphors. We found that the semantic similarity of emotion and taste concepts was greater than that of emotion and color concepts. Importantly, the similarity of taste and emotion concepts was strongly related to their similarity in hedonic valence, a relationship which was also significantly greater than that present between color and emotion. These results suggest that the common core of valence between taste and emotion concepts allows us to bridge the conceptual divide between our shared sensory environment and our internal emotional experience.